Low-temperature hydrogen production and consumption in partially-hydrated peridotites in Oman: implications for stimulated geological hydrogen production - Templeton, Alexis S.; Ellison, Eric T.; Kelemen, Peter B.; Leong, James; Boyd, Eric S.; Colman, Daniel R.; Matter, Juerg M. (Frontiers in Geochemistry, 2024)
The Samail Ophiolite in Oman, the largest exposed body of ultramafic rocks at the Earth’s surface, produces a continuous flux of hydrogen through low-temperature water/rock reactions. In turn, the scale of the subsurface microbial biosphere is sufficient to consume much of this hydrogen, except where H2 is delivered to surface seeps via faults. By integrating data from recent investigations into the alteration history of the peridotites, groundwater dynamics, and the serpentinite-hosted microbial communities, we identify feasible subsurface conditions for a pilot demonstration of stimulated geological hydrogen production. A simple technoeconomic analysis shows that the stimulation methods to be used must increase the rate of net hydrogen production at least 10,000-fold compared to the estimated natural rate to economically produce hydrogen from engineered water/rock reactions in the peridotite formations. It may be possible to meet this challenge within the upper 1–2 km, given the projected availability of reactive Fe(II)-bearing phases and the lower drilling costs associated with shallower operations. Achieving ≥10,000-fold increases in the H2 production rate will require a combination of stimuli. It will likely be necessary to increase the density of fracturing in the reaction volume by at least two orders of magnitude. Then, the H2-production rates must also be increased by another two orders of magnitude by increasing the water/rock ratio and modifying the chemistry of the injected fluids to optimize formation of Fe(III)-bearing secondary phases. These fluid modifications must be designed to simultaneously minimize microbial consumption of H2 within the stimulation volume. In contrast, preserving the high potentials for biological H2 consumption in the shallow groundwaters replete with oxidants such as nitrate, sulfate and dissolved inorganic carbon will reduce the potential for any inadvertent leaks of hydrogen to the atmosphere, where it acts as an indirect greenhouse gas.